Diagnostic accuracy of hyperbilirubinemia in predicting perforated appendicitis - S., Vineed; Hanumanth Naik, R. K. (International Surgery Journal, 2017)
Background: Appendicitis is one of the commonest causes of abdominal pain requiring emergency surgery. Often, it is difficult to reach a proper diagnosis. There may not be classical symptoms and signs of appendicitis. Accurate diagnosis can be aided by additional testing or expectant management or both. These might delay interventions and lead to appendiceal perforation with increased morbidity, mortality and hospital stay. Studies have shown that simple appendicitis has got mortality of 0.3% and perforated appendicitis 6%. Hyperbilirubinemia is a new diagnostic tool for predicting perforation of appendix. The aim of the study is to establish the role of hyperbilirubinemia as a new diagnostic tool to predict perforated appendicitis. Methods: This is a prospective study conducted on 100 consecutive cases of acute appendicitis admitted to the emergency ward. These were subjected to investigations to support the diagnosis. These cases were also subjected to liver function tests and clinical diagnosis was confirmed pre-operative investigations and post-operatively by histopathological examination. Their clinical and investigative data were compiled and analyzed. Statistical analysis was performed using either chi square test or fisher's exact test. The level of significance was set at P <0.05. Results: Total serum bilirubin including both direct and indirect was found to be significantly increased in case of acute suppurative appendicitis. Serum bilirubin was much higher (P <0.000) in cases of gangrenous/perforated appendicitis. Conclusions: Serum bilirubin is an important adjunct in diagnosing the presence of gangrenous/perforated appendicitis.